Obtención experimental del coeficiente difusivo de carne deshidratada (charqui) - Albesa, F. (2016)
The agricultural products simulation requires information about the product behaviour, the diffusive and convective coefficients among others parameters. These coefficients can only be obtained experimentally. At a lab scale it was performed the drying of meet to obtain Charqui, with control and registration of the main variables of the process: temperature, humidity, product weight. It was also performed the estimation of the fresh product area and the dried one trough imagen analysis. The results allowed obtaining the AtHd (diffusive coefficient) and AtHc (convective coefficient) for meat drying. The importance to obtain these parameters is that both can be used in simulation models of the studied process. It remains to perform the mentioned simulations and to evaluate the adjustment for passive solar dryers.